The tale of Cho Ung : a classic of vengeance, loyalty, and romance in Choson Korea - Cho, Sookja (Columbia University Press, 2018)
The Tale of Cho Ung is one of the most widely read and beloved stories of Choson Korea. The anonymously written tale recounts the adventures of protagonist Cho Ung as he overcomes obstacles and grows into a heroic young man. This first translation into English offers a glimpse into early modern Korean vernacular and popular literature.